Design, synthesis, crystal structure and luminescent properties of a new tantalum-phosphate K3BiTaP3O13 with negligible concentration quenching and good thermostability. Issue 3 (4th December 2019) - Zhao, Dan; Xue, Yali; Zhang, Ruijuan; Liu, Baozhong; Fan, Yanping; Dai, Shaojie; Zhang, Shirui; Ma, Zhao
Abstract : This work reports a new host template, K3 BiTaP3 O13, for both Eu 3+ and Tb 3+ luminescence, providing a 'dimensional obstacle' to suppress negative concentration quenching with a high density of Eu 3+ or Tb 3+ . Abstract : The luminous efficiency of rare-earth (Ln 3+ )-doped luminescent materials suffers greatly from the negative concentration quenching effect, which can be surmounted by a large separation of Ln 3+ ions in the host lattice. Herein, this study reports a novel tantalum-phosphate K3 BiTaP3 O13 (KBTP) that possesses a 'chain-like' structure when viewed along the c -axis, containing [TaO(PO4 )2 ]∞, K∞ and [Bi(PO4 )]∞ chains. UV-Vis spectroscopy and density functional theory (DFT) calculations reveal that K3 BiTaP3 O13 has an indirect band-gap of 3.99 eV, making it suitable as a luminescent host matrix. A series of Eu 3+ or Tb 3+ phosphors KBTP: x Eu/Tb ( x = 0.1–1) were prepared and their fluorescent performance was studied. Due to the Bi 3+ ions being far apart in the KBTP host, the negative concentration quenching effect of the prepared phosphors was greatly limited, even when the concentration of Eu/Tb reached up to 80% replacing Bi 3+ . Moreover, both phosphors had good heat-resistance properties at 30–200 °C, keeping 85.6% (KBTP:0.8Eu) and 71.3% (KBTP:0.8Tb) of the initial intensity at 200 °C. These results preliminarily suggest that KBTP is promising as a host material for both Eu 3+ and Tb 3+ fluorescence.